2017
DOI: 10.1097/pcc.0000000000001241
|View full text |Cite
|
Sign up to set email alerts
|

An Intensive, Simulation-Based Communication Course for Pediatric Critical Care Medicine Fellows

Abstract: Objective Effective communication among providers, families, and patients is essential in critical care, but is often inadequate in the pediatric ICU. To address the lack of communication education PCCM fellows receive, the Children’s Hospital of Pittsburgh PICU developed a simulation-based communication course, Pediatric Critical Care Communication Course (PC3). PCCM trainees have limited prior training in communication and will have increased confidence in their communication skills after participating in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 18 publications
1
45
0
14
Order By: Relevance
“…This study confirmed that staff self-reported confidence levels in managing clinical aggression can be increased through completion of a 2-h simulation training programme and adds to the body of literature that simulation training programmes can improve non-technical skills in health care staff: staff confidence [64], communication skills [33,65], leadership skills [66][67][68], team skills [28,69,70], knowledge acquisition and retention [71] and skills in aggression management [37,38,61,72]. The use of a simulated patient exercise to practice de-escalation techniques has been described in some acute care hospitals [12,18,20,21,61] and for undergraduate nursing students [37,38]; however, widespread use of simulation courses for managing aggression in children and young people in acute health care, and in particular paediatric settings, has not been reported until this study.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study confirmed that staff self-reported confidence levels in managing clinical aggression can be increased through completion of a 2-h simulation training programme and adds to the body of literature that simulation training programmes can improve non-technical skills in health care staff: staff confidence [64], communication skills [33,65], leadership skills [66][67][68], team skills [28,69,70], knowledge acquisition and retention [71] and skills in aggression management [37,38,61,72]. The use of a simulated patient exercise to practice de-escalation techniques has been described in some acute care hospitals [12,18,20,21,61] and for undergraduate nursing students [37,38]; however, widespread use of simulation courses for managing aggression in children and young people in acute health care, and in particular paediatric settings, has not been reported until this study.…”
Section: Discussionsupporting
confidence: 78%
“…Simulation training to teach and practice resuscitation and other technical skills is well described in the paediatric acute care literature [28][29][30]. Similarly, the practice of non-technical skills such as communication techniques is also described in the simulation literature [31][32][33]. Simulation-based education may be an effective format to practice de-escalation skills for aggressive behaviour [34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Simulation-based medical education has helped clinicians improve their communication skills, 8 often incorporating standardized actors in medical curricula. 9 Realism is an important concept in simulation; the use of high-fidelity simulators results in improved cognitive performance in pediatric providers. 10 On the other hand, other aspects of realism have been neglected.…”
Section: What This Study Addsmentioning
confidence: 99%
“…We developed a 2‐day communication skills training workshop for paediatric clinicians, faculty members and nurse‐practitioners (NPs) based on a critical care communication (C3) course . Our modifications were targeted towards tailoring the experience to paediatric clinicians and addressing some perceived educational barriers.…”
Section: Introductionmentioning
confidence: 99%
“…We developed a 2 day communication skills training workshop for paediatric clini cians, faculty members and nursepractitioners (NPs) based on a critical care communication (C3) course. 6,7 Our modifications were targeted towards tailoring the experience to paediatric clinicians and addressing some perceived educational barriers. The purposes of this paper are to describe an ICU focused commu nication skills workshop to teach physicians and NPs the core communication skills needed to co lead family centred confer ences, and to assess its feasibil ity and self assessed impact.…”
mentioning
confidence: 99%